2002
DOI: 10.1002/ar.10057
|View full text |Cite
|
Sign up to set email alerts
|

Daily morphological variations in the viscacha (Lagostomus maximus maximus) retina. Probable local modulatory action of melatonin

Abstract: Given that the local melatonin levels exhibit rhythmic daily changes in the retina of the viscacha, we considered it important to study the likely daily variations in morphology and specific 2-[ 125 I]-iodomelatonin binding in retinas from this rodent and to correlate these putative changes with local indole levels. Adult animals of both sexes were captured in their habitat and were kept under a natural photoperiod. For light and electron microscopic studies the viscachas were sacrificed by decapitation at 08:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…In the control viscacha retinas of the present study, we observed ultrastructural changes that demonstrate a daily rhythm of retinal photoreceptor renewal. These results are similar to those previously reported by us for viscachas in their normal habitat [Calderón et al, 2002]. On the contrary, the daily variations in the thickness of the photoreceptor layer, and specifically the outer segments, and ultrastructural variations disappeared completely as a result of the action of lithium, unlike the results reported by Remé et al [1990].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the control viscacha retinas of the present study, we observed ultrastructural changes that demonstrate a daily rhythm of retinal photoreceptor renewal. These results are similar to those previously reported by us for viscachas in their normal habitat [Calderón et al, 2002]. On the contrary, the daily variations in the thickness of the photoreceptor layer, and specifically the outer segments, and ultrastructural variations disappeared completely as a result of the action of lithium, unlike the results reported by Remé et al [1990].…”
Section: Discussionsupporting
confidence: 92%
“…This band lies approximately 3.5 mm above the optic nerve, containing the longest photoreceptors and pigment epithelial cells [Lascano et al, 1999]. The retina of the viscacha exhibits a close temporal relation between melatonin levels, 2[ 125 I]-iodomelatonin binding, and daily morphological changes, as previously demonstrated in our works [Calderón et al, 2001[Calderón et al, , 2002.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…MVBs in terminals may contribute to slow turnover of membrane components of the synaptic terminal (Wittich et al ., 1994). Ultrastructural studies consistently report MVBs in shedding photoreceptor cells (Calderon et al ., 2002; Calman and Chamberlain, 1982; Williams and Blest, 1980; Schmied and Holtzman, 1987). MVB numbers can fluctuate in parallel with circadian shedding and synthesis of the photoreceptor membrane (Williams and Blest, 1980; Calderon et al ., 2002; Chamberlain and Barlow, 1984; LaVail, 1976).…”
Section: Distribution Of Mvbs In Neuronal Compartmentsmentioning
confidence: 86%
“…Melanin pigment granule distribution in the RPE varies individually during the light-dark cycle (Pang and Yew 1979;Calderon et al 2002), so that granules are dispersed throughout the cytoplasm during the day (maximum dispersion at 1600 hours) and aggregated in the apical part of the cells at night (maximum aggregation at 2400 hours; Calderon et al 2002). All our specimens were killed early in the morning (0800-0900 hours) but, in contrast to observations by Calderon et al (2002), the stage of melanin dispersion was not the same in all epithelial cells. Indeed, we observed that pigment granules were dispersed near the ora serrata and congregated near the posterior pole of the eye.…”
Section: Retinamentioning
confidence: 99%